FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENGGUNAAN APD PADA TENAGA KESEHATAN DI MASA PANDEMI COVID-19 UPTD. PUSKESMAS MELINTANG : Gita Fajrianti (Biro Riset, Inovasi dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2021)
Personal protective equipment (PPE) is a tool used by health workers to protect patients from microorganisms that exist in health workers, PPE equipment used by health workers to protect themselves during work. The PPE used is expected to be PPE that has met the standards so that it is effective in preventing the spread of the virus or contracting Covid-19. According to Melintang Public Health Centre compliance level in the use of PPE in 2019 was 80%, which was the lowest level of compliance with the use of PPE among other health centers, but in 2020, during the COVID-19 pandemic, compliance with the use of PPE reached 100%. The purpose of this study was to determine the factors related to compliance with the use of PPE in health workers during the Covid-19 pandemic Melintang Public Health Centre. This research uses a cross-sectional in the Melintang Public Health Centre. The population in this study were 67 health workers with the research sample being the total population. The research instrument used is a quantitative approach and interview methods as well as measuring tools through questionnaires. The results showed that there was a significant relationship between knowledge with p value = 0.020, attitude with p value = 0.034, availability of PPE with p value = 0.007, motivation with p value = 0.005 and supervision with p value = 0.023 towards compliance with PPE use in workers. Health During the Covid-19 Pandemic. As for the education variable, the chi square test cannot be done. Suggested the need to increase employee motivation by giving rewards to employees who always comply with using PPE correctly and completely, increasing knowledge about the importance of using PPE compliance to prevent transmission of Covid-19 through socialization to health workers, checking and monitoring by K3 officers regarding the completeness of the availability of PPE in each room